The division problem with maximal capacity constraints - Gustavo Berganti\~nos; Jordi Massó; Alejandro Neme (SERIEs - Journal of the Spanish Economic Association, 2012)
The division problem consists of allocating a given amount of an homogeneous and perfectly divisible good among a group of agents with singlepeaked preferences on the set of their potential shares. A rule proposes a vector of shares for each division problem. Most of the literature has implicitly assumed that all divisions are feasible. In this paper we consider the division problem when each agent has a maximal capacity due to an objective and verifiable feasibility constraint which imposes an upper bound on his share. Then each agent has a feasible interval of shares where his preferences are single-peaked. A rule has to propose to each agent a feasible share.We focus mainly on strategy-proof, efficient and consistent rules and provide alternative characterizations of the extension of the uniform rule that deals explicitly with agents' maximal capacity constraints.
Keywords: D71; 330; division problem; single-peaked preferences; uniform rule; capacity constraints; Öffentliche Güter; Unteilbarkeit; Allokation; Abstimmungsregel; Neue politische Ökonomie; Theorie